Lesson Study Oriented Teaching Materials Improve Student Learning Outcomes - I Gede Nurjaya; I Gusti Ayu Agung Manik Wulandari (Universitas Pendidikan Ganesha, 2023)
The ineffectiveness of learning is influenced by learning resource factors such as the unavailability of teaching materials. Based on this, this research aims to develop lesson study-oriented textbooks for educational technology students. This type of research is development research. This study used a one-group pretest, posttest design pre-experimental design. The textbook was developed using the Hannafin & Peck model. The products developed were assessed by content experts, media experts, and learning design experts. The product trial subjects were 38 educational technology students. The data collection method used is the questionnaire method, the test method, and the observation method. Data collection instruments used questionnaires and tests. The collected data were then analyzed using qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistical analysis (t-test). The research results show that lesson study-oriented textbooks get very good qualifications from experts and students. The results of the analysis also show that there are significant differences in student learning outcomes before and after using textbooks. It was concluded that lesson study-oriented textbooks improve student learning outcomes.